A friction material interface self-repairing performance testing method and system
By building a test platform and self-repair performance evaluation system on the friction interface of copper-based powder metallurgical materials, simulating the self-repair process and analyzing the performance characterization parameters, the problem of failure to effectively evaluate self-repair performance in the existing technology is solved, and the system evaluation and working condition optimization of self-repair performance are achieved.
Patent Information
- Application Number
- CN202210277418.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-03-15
AI Technical Summary
The prior art has failed to effectively evaluate and verify the self-repair performance of the friction interface of copper-based powder metallurgical materials, and lacks a systematic self-repair performance evaluation system and experimental characterization method.
A method of self-repair performance testing of friction materials interfaces is adopted, and a self-repair performance evaluation index system is established by building a test platform to conduct damage simulation tests on the sample, including mean square variance of friction coefficient, surface roughness, furrow depth and width, and surface hardness of the damage boundary, etc., to simulate the self-repair process and analyze the self-repair performance characterization parameters and time change laws.
A comprehensive self-repair parameter evaluation system has been established, which can effectively analyze the impact of multiple factors on the self-repair performance of materials, determine the fastest self-repair working conditions, and improve the accuracy and comprehensiveness of self-repair performance testing.
Smart Images

Figure CN114705519B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of friction material performance testing, and in particular to a friction material interface self-repairing performance testing method and system. Background Art
[0002] Friction materials are components used in mechanical equipment to perform braking and transmission functions. The main materials are asbestos friction materials and non-asbestos friction materials. Powder metallurgy friction materials in non-asbestos friction materials are widely used in transportation tools such as airplanes and trucks, as well as high-power heavy-duty engineering machinery due to their good corrosion resistance, heat dissipation and thermal conductivity; among them, copper-based powder metallurgy materials are the most widely used because they are not prone to bonding.
[0003] The friction and wear characteristics of the interface of copper-based powder metallurgy materials will affect the reliability of component operation and the life of equipment. The unclear evolution law of the "damage-self-repair" process, unclear self-repair mechanism, and imperfect characterization system have restricted the improvement of the reliability and life of large-scale key equipment. Under normal working conditions, the friction interface often wears out, resulting in slight scratches or annular furrows on the interface, but after the action of the lubricating components inside the friction material, the interface will gradually self-repair; but when the friction interface undergoes this process for a long time, the furrows will eventually fail to heal, the matrix and friction components will gradually peel off, and the working life of the component will end.
[0004] At present, many scholars have conducted research on the friction properties of powder metallurgy materials. Some scholars have studied the friction and wear properties of copper-based powder metallurgy materials at different initial braking velocities and the friction and wear properties of copper-based powder metallurgy materials at constant speeds; other scholars have studied the surface temperature and friction coefficient of copper-based powder metallurgy materials under different braking pressures; and some scholars have studied the wear and wear of copper-based powder metallurgy materials under dry sliding conditions, as well as the friction properties of copper-based powder metallurgy materials under running-in and non-running-in conditions. However, the above studies did not consider the self-repairing properties of copper-based powder metallurgy materials themselves, lacked a more systematic evaluation system for the self-repairing properties of friction materials, and did not propose experimental characterization and verification methods to find the influencing law of the self-repairing properties of the friction interface. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a method and system for testing the self-repairing performance of a friction material interface, which can obtain the influencing law of the self-repairing performance and determine the fastest self-repairing working condition.
[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a method for testing the self-repair performance of a friction material interface, which comprises: building a test platform, performing a damage simulation test on a sample, and obtaining a damaged sample with a preset damage degree; based on characterization parameters, performing a self-repair test on the damaged sample, simulating the self-repair process of the damaged sample with a preset damage degree; determining whether the self-repair is completed, obtaining the self-repair performance characterization parameters and the self-repair time change law, and completing the self-repair performance test.
[0007] Furthermore, the test platform is constructed to conduct damage simulation tests on samples, including:
[0008] The test platform was built by a friction and wear testing machine, and a grinding pin was used to produce slight plowing wear due to hard abrasive wear;
[0009] A plurality of damaged samples were prepared under the same working conditions, and the furrow depth and width of all damaged samples were kept within the standard range to prepare damaged samples.
[0010] Furthermore, the characterization parameters include mean square error of friction coefficient, surface roughness, furrow width and depth, and damage boundary surface hardness.
[0011] Further, the self-repair test on the damaged sample includes:
[0012] A self-healing performance evaluation index system was established by characterizing parameters, including the width and depth of the damaged area, surface roughness, friction coefficient, and damage boundary hardness;
[0013] Under certain working conditions, the surface morphology, surface hardness of the damaged boundary, and metallographic microscopic imaging information are obtained after sliding and rubbing gradually at different times, and the friction coefficient of the whole process is collected synchronously;
[0014] In the initial state of self-repair, the contour of the furrow part is clear, and the furrow width and depth are the preset values; the surface roughness is the maximum value of the self-repair process; at the same time, the friction coefficient fluctuates within a fixed range, and the fluctuation degree of the mean square error S of the friction coefficient is within the preset range, indicating that the friction stability is poor; the surface hardness of the damaged boundary is the minimum value of the self-repair process;
[0015] During the self-repair process of sliding friction, as the sliding friction time increases, the damage boundary of the furrow part gradually becomes blurred, the width and depth of the furrow gradually decrease, and the reduction rate is fastest in the initial stage of sliding friction; the friction coefficient decreases, and the mean square error S of the friction coefficient decreases, indicating that the stability of the friction system is improved; the surface hardness of the damaged boundary first decreases and then quickly recovers; at the same time, as the sliding friction time increases, friction components such as SiC and SiO2 are exposed, and the boundary between the blurred and clear damage boundary gradually becomes blurred, verifying the effectiveness of the characterization of the furrow width, depth and surface hardness parameters of the damaged boundary.
[0016] Further, the determining whether the self-repair is completed includes:
[0017] When the sliding reaches the final stage, the furrow part is difficult to distinguish, the width and depth drop to lower values and remain stable, and the surface roughness also drops to the lowest level;
[0018] The friction coefficient gradually stabilizes, and the mean square error of the friction coefficient also drops to the minimum value, indicating that the friction stability has reached an ideal state; the surface hardness of the damaged boundary has also reached the maximum value;
[0019] Through metallographic microscopy, it was found that at the end of the self-repair stage, a hard oxide film would appear on the interface, the non-metallic components would be filled more evenly, and the self-repair of the material would be completed.
[0020] Furthermore, the metallographic microscopic imaging analysis shows that natural flake graphite and MoS2 have diffusivity and fluidity. When the friction interface is sliding, natural flake graphite and MoS2 will slide and fill the damaged area after being compressed. By observing the metallographic image of the damaged boundary, it can be determined whether the self-repair process is completed.
[0021] Furthermore, the self-repair performance characterization parameters and the self-repair time variation law are obtained, including: analyzing temperature, The parameters characterizing the self-repair performance and the changing rules of the self-repair time under the influence of rotation speed and pressure;
[0022] The friction samples are rubbed at different temperatures, speeds and pressures for a fixed time to obtain the friction coefficient and surface morphology self-repair information, and the self-repair performance characterization parameters are calculated; the friction samples after sliding are continued to slide under the original working conditions until the self-repair performance characterization parameters show a consistent judgment trend, that is, they reach the self-repair point, and the self-repair time is counted to obtain the change rules of temperature, speed, pressure and self-repair time respectively.
[0023] A friction material interface self-repair performance test system comprises: a sample production module, which builds a test platform and performs damage simulation tests on samples to obtain damaged samples with a preset damage degree; a self-repair module, which performs self-repair tests on damaged samples based on characterization parameters to simulate the self-repair process of damaged samples with a preset damage degree; a change law acquisition module, which determines whether self-repair is completed, obtains self-repair performance characterization parameters and self-repair time change laws, and completes self-repair performance testing.
[0024] A computer-readable storage medium storing one or more programs, wherein the one or more programs include instructions, which, when executed by a computing device, cause the computing device to perform any of the above methods.
[0025] A computing device comprises: one or more processors, a memory and one or more programs, wherein the one or more programs are stored in the memory and configured to be executed by the one or more processors, and the one or more programs include instructions for executing any of the above methods.
[0026] The present invention adopts the above technical solution, which has the following advantages:
[0027] 1. The present invention establishes a self-repair parameter evaluation system, including: friction coefficient, surface roughness, furrow depth and width, surface hardness. The comprehensive index is better than any single factor in judging the self-repair effect, and the conclusion is accurate.
[0028] 2. The present invention can comprehensively analyze the influence of multiple factors on the self-repairing performance of materials.
[0029] 3. The present invention can achieve the fastest self-repairing working condition. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is an overall flow chart of the method for testing the self-repairing performance of the friction material interface in an embodiment of the present invention;
[0031] Figure 2 is a surface topography diagram of a friction plate in an embodiment of the present invention;
[0032] Figure 3 is a schematic diagram of the hardness measurement point arrangement in an embodiment of the present invention;
[0033] Figure 4 is an evaluation system diagram in an embodiment of the present invention;
[0034] Figure 5 is a metallographic micrograph of the damaged area in an embodiment of the present invention;
[0035] Figure 6 It is a schematic diagram of the structure of a computing device in one embodiment of the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the According to the exemplary embodiments of the present application. As used herein, unless the context clearly indicates otherwise, the singleThe number form is also intended to include the plural form. In addition, it should be understood that when the terms "include" and / or "comprises" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or their combinations.
[0038] The present invention provides a method and system for testing the self-repairing performance of a friction material interface. The test object of the present invention is a friction interface of a copper-based powder metallurgy material. The self-repairing performance change law of the friction interface of the material is tested, and the friction interface self-repairing performance characterization parameters and methods based on multiple indicators such as the mean square error of the friction coefficient, surface roughness, surface hardness of the damage boundary, furrow depth and width are constructed. The self-repairing performance of the copper-based powder metallurgy material is verified by a damage test simulating slight furrow wear on the interface and a disk-on-disk test simulating the self-repairing process of the friction interface. At the same time, through the tests of ambient temperature, rotation speed and pressure, the influencing law on the self-repairing performance is found, and the changes in the damage area accompanying the self-repairing process are analyzed, providing a reference basis for the better application of the self-repairing performance of copper-based powder metallurgy materials in engineering practice.
[0039] In one embodiment of the present invention, a method for testing the self-repairing performance of a friction material interface is provided. This embodiment uses the method applied to a terminal as an example. It is understandable that the method can also be applied to a server, and can also be applied to a system including a terminal and a server, and is implemented through the interaction between the terminal and the server. In this embodiment, Figure 1 As shown, the method comprises the following steps:
[0040] 1) Build a test platform and conduct damage simulation tests on samples to obtain samples with preset damage levels to simulate sample damage, such as slight damage to the friction disc interface;
[0041] 2) Based on the characterization parameters, a self-repair test is performed to simulate the self-repair process of a sample with a preset damage degree;
[0042] 3) Determine whether the self-repair is completed, obtain the self-repair performance characterization parameters and the change law of the self-repair time, complete the self-repair performance test, and determine the difference in self-repair performance under the influence of different factors.
[0043] In the above step 1), a test platform is built to perform a damage simulation test on the sample. The purpose of the test is to simulate the slight plowing wear on the surface of the friction disc due to hard abrasive wear; the following steps are included:
[0044] 1.1) The test platform was built by a friction and wear testing machine, and a grinding pin was used to produce slight plowing wear caused by hard abrasive wear;
[0045] In this embodiment, the test materials include a friction disc and a dual steel disc, and a grinding pin is used to simulate the surface hard abrasive wear to produce furrow wear. Since the grinding pin is positioned higher than the steel sheet by a certain distance, a local grinding effect is produced on the friction disc when the disc rotates and rubs.
[0046] In order to make the damage simulation process more feasible, the grinding pin and steel sheet should be made of materials with a hardness much greater than that of the friction disc. During the production process, multiple damaged samples are prepared under the same working conditions, and the furrow depth and width of the damaged samples are ensured to be within the same standard range.
[0047] The specific steps are:
[0048] (1) Focus the friction and wear testing machine to ensure the wear accuracy of the friction disc;
[0049] (2) Dry the new friction disc and install all parts;
[0050] (3) Set the loading force, motor target speed, running time, and temperature of the test piece;
[0051] (4) After the temperature stabilizes, combine the upper friction disc and the lower steel sheet;
[0052] (5) Record the friction coefficient;
[0053] (6) Stop the test, separate the friction pair, clean the friction disc, and cool and dry it.
[0054] Observe the damaged samples produced by white light interferometer and electron microscope to determine whether they meet the requirements of furrow wear. If not, repeat the above steps to continue preparation.
[0055] 1.2) Prepare multiple damaged samples under the same working conditions (such as ambient temperature, rotation speed, pressure, sliding time, etc.), and keep the furrow depth and width of all damaged samples within the standard range to prepare damaged samples;
[0056] Among them, the standard range is preferably 46.400 μm±10% and 1760 μm±10%.
[0057] In the above step 2), the characterization parameters include mean square error of friction coefficient, surface roughness, furrow width and depth, and surface hardness of damage boundary.
[0058] Among them, the mean square deviation S of the friction coefficient is: During the test, the testing machine can monitor and record the friction coefficient μ of the friction plate in real time. After the test, the mean square deviation S of the friction coefficient is calculated by the following formula to characterize the stability of the friction system.
[0059]
[0060] In the formula, n is the number of sampling points, ui is the friction coefficient at the i-th sampling time, is the average value of the friction coefficient.
[0061] The surface roughness Ra is: After the test, the surface roughness Ra is measured using a white light interferometer. The white light interferometer is an optical instrument that measures the optical path difference in a non-contact manner to determine the relevant physical quantities. The surface roughness R is calculated using the built-in calculation formula of the white light interferometer. a , to characterize the size change of surface micro-protrusions:
[0062]
[0063] Where A is the area of the measurement region and Z(x,y) is the depth of the point (x,y) in the measurement region.
[0064] The furrow width W and depth H are: The surface morphology of the friction plate after the self-repairing test was observed using a white light interferometer, as shown in Figure 2 As shown in the figure. Based on the three-dimensional topography, the contour line of the cross-sectional furrow is generated. The distance between the starting point and the end point is the furrow width W, and the distance between the lowest point and the horizontal line where the starting point and the end point are located is the furrow depth H. The furrow width and depth values can reflect the overall size change of the damaged furrow, thereby characterizing the evolution degree of the self-healing process.
[0065] The surface hardness D of the damage boundary is: the hardness range of the friction disk material is 20-50HRF. In this embodiment, a Rockwell hardness tester is used to measure the surface hardness of the friction disk to characterize the component migration and metal oxidation degree at the damage boundary, thereby proving the evolution law of the self-healing performance. The arrangement of the measurement points is as follows: Figure 3 As shown, the location is selected at the furrow damage boundary, 5 test points are randomly selected to measure the hardness value, and the average value is calculated as the surface hardness value of the damage boundary.
[0066] In this embodiment, a test platform built by a friction and wear testing machine is used to conduct a disk-to-disk friction test to explore the self-repair process of samples with a specific degree of damage. The self-repair test of the damaged sample includes the following steps:
[0067] 2.1) Establish a self-healing performance evaluation index system by characterizing parameters, including the width and depth of the damaged area, surface roughness, friction coefficient, and damage boundary hardness, such as Figure 4 As shown; by measuring these evaluation indicators, the effects of ambient temperature, rotation speed, pressure, material ratio and initial surface state on the self-healing properties of friction materials are explored.
[0068] 2.2) Under the determined working conditions (such as ambient temperature, rotational speed, pressure, etc.), gradually perform sliding friction at different times to obtain surface topography, damage boundary surface hardness, metallographic microscopic imaging information, and synchronously collect the friction coefficient throughout the process;
[0069] Specifically, apply the damaged samples prepared in the first-stage test, and perform sliding friction for a min, b min, c min, d min, e min, f min (a < b < c < d < f) respectively under the determined working conditions (ambient temperature, rotational speed, pressure) to obtain information such as surface topography, damage boundary surface hardness, and metallographic microscopic imaging, and synchronously collect the friction coefficient throughout the process; In order to corroborate the characterization of the self-healing performance and the determination of the self-healing time, an electron microscope can be used to compare the metallographic micrographs at different times, as Figure 5 shown.
[0070] 2.3) At the initial state of self-healing, the contour of the plow groove part is clear, and the width and depth values of the plow groove are preset values. The preset value at the initial state is the maximum value of the width and depth values of the plow groove; the surface roughness is the maximum value during the self-healing process; at the same time, the friction coefficient fluctuates up and down within a fixed range, and the fluctuation degree of the mean square deviation S of the friction coefficient is within the preset range, indicating poor friction smoothness; the damage boundary surface hardness D is the lowest value during the self-healing process; it can be seen from the electron microscope that there are many micro-scratches at the damaged part in the initial stage of self-healing, the damage boundary is clear, the size of the plow groove is large and the bottom surface structure is relatively loose.
[0071] Among them, the preset value of the plow groove width does not exceed 3 mm, and the preset value of the depth value does not exceed 100 μm; to ensure the test accuracy, the maximum value of the preset range of the fluctuation degree of the mean square deviation S of the friction coefficient does not exceed 1×10 -2 .
[0072] 2.4) During the self-healing process of sliding friction, as the sliding friction time increases, the damage boundary of the plow groove part gradually becomes blurred, the width and depth of the plow groove gradually decrease, and the reduction rate is the fastest in the initial stage of sliding friction; the friction coefficient decreases, and the mean square deviation S of the friction coefficient decreases, indicating an improvement in the stability of the friction system; due to the diffusion and overflow of the lubricating components in the initial stage of self-healing, the damage boundary surface hardness D first decreases and then rapidly rebounds; at the same time, as the sliding friction time increases, friction components such as SiC and SiO2 are exposed, and the boundary between the blurred and clear damage boundaries gradually becomes blurred, verifying the effectiveness of the parameters of the plow groove width, depth, and damage boundary surface hardness.
[0073] Among them, the main reason for the initial decrease in the damage boundary surface hardness D is the diffusion and overflow of the lubricating components (natural flake graphite, MoS2, etc.) under the action of pressure and temperature in the early stage of self-healing, and the main reason for the rebound is the formation of a metal oxide film and a new phase of mineral compounds in the later stage of self-healing.
[0074] In the above step 3), determining whether the self-repair is completed includes the following steps:
[0075] 3.1) When the sliding reaches the final stage, the furrow part is difficult to distinguish, the width and depth drop to lower values and remain stable, and the surface roughness also drops to the lowest level;
[0076] 3.2) The friction coefficient gradually stabilizes, and the mean square error of the friction coefficient also drops to the minimum value, indicating that the friction stability has reached Ideal state; the surface hardness of the damage boundary also reaches the maximum value;
[0077] 3.3) Metallographic microscopy shows that at the end of the self-repair stage, a hard oxide film appears on the interface and the non-metallic components are filled more evenly, which confirms the increase in hardness and friction stability of the damaged area, and the self-repair of the material is completed.
[0078] Among them, the metallographic microscopic imaging analysis shows that natural flake graphite and MoS2 have diffusivity and fluidity. When the friction interface is sliding, natural flake graphite and MoS2 will slide and fill into the damaged area after being compressed. By observing the metallographic image of the damaged boundary, it can be determined whether the self-repair process is completed.
[0079] In the above step 3), the self-repair performance characterization parameters and the self-repair time variation law are obtained, including: analyzing the self-repair performance characterization parameters and the self-repair time variation law under the influence of temperature, rotation speed and pressure;
[0080] The friction samples are rubbed at different temperatures, speeds and pressures for a fixed time to obtain the friction coefficient and surface morphology self-repair information, and the self-repair performance characterization parameters are calculated; the friction samples after sliding are continued to slide under the original working conditions until the self-repair performance characterization parameters show a consistent judgment trend, that is, they reach the self-repair point, and the self-repair time is counted to obtain the change rules of temperature, speed, pressure and self-repair time respectively.
[0081] In this embodiment, since the self-repairing performance of the friction material is related to multiple factors, such as ambient temperature, rotation speed, pressure, material ratio, and initial surface state, etc., taking the influence of temperature, rotation speed, and pressure on the self-repairing performance as an example, three groups of disc-to-disc sliding self-repairing tests A, B, and C are designed to analyze the variation law of the self-repairing performance characterization parameters and self-repairing time under the influence of the three factors.
[0082] (1) Temperature influence:
[0083] In the disc-to-disc sliding self-repair test, the speed and pressure are fixed. The ambient temperatures are a1℃, a2℃, a3℃, and a4℃, and the test numbers correspond to A1, A2, A3, and A4, respectively. The four friction samples slide at different temperatures for a fixed time to obtain self-repair information such as friction coefficient and surface morphology, and calculate the self-repair performance characterization parameters. The friction samples after sliding continue to slide according to the original working conditions until the self-repair performance characterization parameters show a consistent judgment trend, that is, they reach the self-repair point, and the self-repair time is calculated.
[0084] (2) Influence of rotation speed:
[0085] In order to study the effect of rotation speed on the self-healing performance of materials, the ambient temperature and pressure were fixed. The sliding speeds were b1r / min, b2 r / min, b3 r / min, and b4 r / min, and the test numbers corresponded to B1, B2, B3, and B4, respectively. The four friction samples were all rubbed for a fixed time, and the self-repairing information such as friction coefficient and surface morphology were statistically analyzed, and the changes in the parameters characterizing the self-repairing performance were recorded. The friction samples after sliding continued to slide according to the original working conditions until the parameters characterizing the self-repairing performance showed a consistent judgment trend, that is, they reached the self-repair point, and the self-repairing time was statistically analyzed.
[0086] (3) Pressure influence:
[0087] The ambient temperature and speed are fixed, and the pressures are c1N, c2N, c3N, and c4N, respectively. The test numbers correspond to C1, C2, C3, and C4, respectively. The four friction samples are rubbed for a fixed time to obtain self-repair information such as friction coefficient and surface morphology. Computational self-healing The friction sample after sliding is rubbed again under the original working condition until the self-repair performance The characterization parameters show a consistent judgment trend, that is, the self-repair point is reached and the self-repair time is counted.
[0088] In one embodiment of the present invention, a friction material interface self-repairing performance testing system is provided, which comprises:
[0089] Sample production module, builds a test platform, conducts damage simulation tests on samples, and obtains damaged samples with preset damage levels;
[0090] The self-repair module conducts self-repair tests on damaged samples based on the characterization parameters, simulating the self-repair process of damaged samples with a preset damage degree;
[0091] The change law acquisition module determines whether the self-repair is completed, obtains the self-repair performance characterization parameters and the change law of the self-repair time, and completes the self-repair performance test.
[0092] The system provided in this embodiment is used to execute the above-mentioned method embodiments. Please refer to the above-mentioned embodiments for specific processes and detailed contents, which will not be repeated here.
[0093] like Figure 6 As shown, it is a schematic diagram of the structure of a computing device provided in an embodiment of the present invention. The computing device can be a terminal, which can include: a processor, a communication interface, a memory, a display screen and an input device. Among them, the processor, the communication interface and the memory complete mutual communication through a communication bus. The processor is used to provide computing and control capabilities. The memory includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system and a computer program. When the computer program is executed by the processor, a performance testing method is implemented; the internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The communication interface is used to communicate with an external terminal in a wired or wireless manner. The wireless manner can be realized through WIFI, a management network, NFC (near field communication) or other technologies. The display screen can be a liquid crystal display screen or an electronic ink display screen. The input device can be a touch layer covered on the display screen, or a key, trackball or touchpad set on the housing of the computing device, or an external keyboard, touchpad or mouse. The processor can call the logic instructions in the memory to execute the following method: build a test platform, conduct a damage simulation test on the sample, and obtain a sample with a preset damage degree to simulate the damage of the sample, such as slight damage to the friction disk interface; based on the characterization parameters, conduct a self-repair test to simulate the self-repair process of the sample with a preset damage degree; determine whether the self-repair is completed, obtain the self-repair performance characterization parameters and the change law of the self-repair time, complete the self-repair performance test, and determine the difference in self-repair performance under the influence of different factors.
[0094] In addition, the logical instructions in the above-mentioned memory can be implemented in the form of software functional units and can be stored in a computer-readable storage medium when sold or used as an independent product. Based on this understanding, the technical solution of the present invention can be essentially or partly embodied in the form of a software product that contributes to the prior art. The computer software product is stored in a storage medium and includes several instructions for enabling a computer device (which can be a personal computer, server, or network device, etc.) to perform all or part of the steps of the method described in each embodiment of the present invention. The aforementioned storage media include: USB flash drives, mobile hard disks, read-only memories (ROM), random access memories (RAM), and the like. Memory), disks or optical disks, etc. A medium storing program code.
[0095] Those skilled in the art will understand that Figure 6The structure shown in the figure is only a block diagram of a part of the structure related to the scheme of the present application, and does not constitute a limitation on the computing device to which the scheme of the present application is applied. The specific computing device may include more or fewer components than shown in the figure, or combine certain components, or have a different arrangement of components.
[0096] In one embodiment of the present invention, a computer program product is provided, wherein the computer program product comprises a computer program stored on a non-transitory computer-readable storage medium, wherein the computer program comprises program instructions. When the program instructions are executed by a computer, the computer can execute the methods provided by the above-mentioned method embodiments, for example, comprising: building a test platform, performing a damage simulation test on a sample, and obtaining a sample with a preset damage degree to simulate the damage of the sample, such as slight damage to the friction disk interface; performing a self-repair test based on characterization parameters to simulate the self-repair process of the sample with a preset damage degree; determining whether the self-repair is completed, obtaining the self-repair performance characterization parameters and the self-repair time variation law, completing the self-repair performance test, and determining the difference in self-repair performance under the influence of different factors.
[0097] In one embodiment of the present invention, a non-transitory computer-readable storage medium is provided, which stores server instructions. The computer instructions enable a computer to execute the methods provided in the above embodiments, for example, including: building a test platform, performing a damage simulation test on a sample, and obtaining a sample with a preset damage degree to simulate the damage of the sample, such as slight damage to the friction disk interface; based on the characterization parameters, performing a self-repair test to simulate the self-repair process of the sample with a preset damage degree; determining whether the self-repair is completed, obtaining the self-repair performance characterization parameters and the self-repair time change law, completing the self-repair performance test, and determining the difference in self-repair performance under the influence of different factors.
[0098] The above embodiment provides a computer-readable storage medium, whose implementation principle and technical effect are similar to those of the above method embodiment, and will not be repeated here.
[0099] The present application is described with reference to the flowcharts and / or block diagrams of the methods, devices (systems), and computer program products according to the embodiments of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of the processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor, or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.
[0100] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.
[0101] These computer program instructions can also be loaded into a computer or other programmable data processing device so that A sequence of steps performed on a computer or other programmable device to produce a computer-implemented process. Instructions executed on a computer or other programmable device provide instructions for implementing the process Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for testing the self-repairing performance of a friction material interface, characterized in that: include: Build a test platform, conduct damage simulation tests on samples, and obtain damaged samples with preset damage levels; Based on the characterization parameters, a self-repair test is conducted on the damaged sample to simulate the self-repair process of the damaged sample with a preset damage degree; Determine whether the self-repair is completed, obtain the self-repair performance characterization parameters and the self-repair time change law, and complete the self-repair performance test; The characterization parameters include mean square error of friction coefficient, surface roughness, furrow width and depth, and damage boundary surface hardness; The self-repair test on the damaged sample comprises: A self-healing performance evaluation index system was established by characterizing parameters, including the width and depth of the damaged area, surface roughness, friction coefficient, and damage boundary hardness; Under certain working conditions, the surface morphology, surface hardness of the damaged boundary, and metallographic microscopic imaging information are obtained after sliding and rubbing gradually at different times, and the friction coefficient of the whole process is collected synchronously; In the initial state of self-repair, the contour of the furrow part is clear, and the furrow width and depth are the preset values; the surface roughness is the maximum value of the self-repair process; at the same time, the friction coefficient fluctuates within a fixed range, and the fluctuation degree of the mean square error S of the friction coefficient is within the preset range, indicating that the friction stability is poor; the surface hardness of the damaged boundary is the minimum value of the self-repair process; During the self-repair process of sliding friction, as the sliding friction time increases, the damage boundary of the furrow gradually becomes blurred, the width and depth of the furrow gradually decrease, and the reduction rate is fastest in the initial stage of sliding friction; the friction coefficient decreases, and the mean square error S of the friction coefficient decreases, indicating that the stability of the friction system is improved; the surface hardness of the damaged boundary first decreases, and then quickly recovers; at the same time, as the sliding friction time increases, the SiC and SiO2 friction components are exposed, and the boundary between the blurred and clear damage boundary gradually becomes blurred, which verifies the effectiveness of the characterization of the furrow width, depth and damage boundary surface hardness parameters; The determining whether the self-repair is completed includes: When the sliding reaches the final stage, the furrow part is difficult to distinguish, the width and depth drop to lower values and remain stable, and the surface roughness also drops to the lowest level; The friction coefficient gradually stabilizes, and the mean square error of the friction coefficient also drops to the minimum value, indicating that the friction stability has reached an ideal state; the surface hardness of the damaged boundary has also reached the maximum value; Through metallographic microscopy, it was found that at the end of the self-repair stage, a hard oxide film would appear on the interface, the non-metallic components would be filled more evenly, and the self-repair of the material would be completed.
2. The method for testing the self-repairing performance of the friction material interface according to claim 1, characterized in that: The test platform is constructed to conduct damage simulation test on the sample, including: The test platform was built by a friction and wear testing machine, and a grinding pin was used to produce slight plowing wear due to hard abrasive wear; A plurality of damaged samples were prepared under the same working conditions, and the furrow depth and width of all damaged samples were kept within the standard range to prepare damaged samples.
3. The method for testing the self-repairing performance of the friction material interface according to claim 1, characterized in that: The determining whether the self-repair is completed includes: When the sliding reaches the final stage, the furrow part is difficult to distinguish, the width and depth drop to lower values and remain stable, and the surface roughness also drops to the lowest level; The friction coefficient gradually stabilizes, and the mean square error of the friction coefficient also drops to the minimum value, indicating that the friction stability has reached an ideal state; the surface hardness of the damaged boundary has also reached the maximum value; Through metallographic microscopy, it was found that at the end of the self-repair stage, a hard oxide film would appear on the interface, the non-metallic components would be filled more evenly, and the self-repair of the material would be completed.
4. The method for testing the self-repairing performance of the friction material interface according to claim 1, characterized in that: The metallographic microscopic imaging analysis shows that natural flake graphite and MoS2 have diffusivity and fluidity. When the friction interface is sliding, natural flake graphite and MoS2 will slide and fill the damaged area after being compressed. By observing the metallographic image of the damaged boundary, it can be determined whether the self-repair process is completed.
5. The method for testing the self-repairing performance of the friction material interface according to claim 1, characterized in that: The obtaining of the self-repairing performance characterization parameters and the self-repairing time variation law comprises: analyzing the self-repairing performance characterization parameters and the self-repairing time variation law under the influence of temperature, rotation speed and pressure; The friction samples are rubbed at different temperatures, speeds and pressures for a fixed time to obtain the friction coefficient and surface morphology self-repair information, and the self-repair performance characterization parameters are calculated; the friction samples after sliding are continued to slide under the original working conditions until the self-repair performance characterization parameters show a consistent judgment trend, that is, they reach the self-repair point, and the self-repair time is counted to obtain the change rules of temperature, speed, pressure and self-repair time respectively.
6. A friction material interface self-repairing performance testing system, used to implement the friction material interface self-repairing performance testing method as claimed in any one of claims 1 to 5, characterized in that: include: Sample production module, builds a test platform, conducts damage simulation tests on samples, and obtains damaged samples with preset damage levels; The self-repair module conducts self-repair tests on damaged samples based on the characterization parameters, simulating the self-repair process of damaged samples with a preset damage degree; The change law acquisition module determines whether the self-repair is completed, obtains the self-repair performance characterization parameters and the change law of the self-repair time, and completes the self-repair performance test.
7. A computer-readable storage medium storing one or more programs, characterized in that: The one or more programs include instructions, which, when executed by a computing device, cause the computing device to perform any one of the methods of claims 1 to 5.
8. A computing device, characterized in that include: One or more processors, a memory, and one or more programs, wherein the one or more programs are stored in the memory and configured to be executed by the one or more processors, and the one or more programs include instructions for executing any one of the methods described in claims 1 to 5.
Citation Information
Patent Citations
Self-repair conductive abrasion-resistant copper alloy for high-speed rail grounding device and preparation method for self-repair conductive abrasion-resistant copper alloy
CN106756215A
Wear-resistant wheat straw composite board and preparation method thereof
CN113429584A